Teaching and learning of accounting ethics education / Marzlin Marzuki - Marzuki, Marzlin (Faculty of Accountancy, UiTM Kedah, 2018)
The discussions on teaching and learning of ethics education have been well debated and received much attention by various interested parties. In fact, the phrase “ethics education” has a variety of interpretations. According to Dellaportas et al. (2005, p. 28), some refer to ethics education as instruction to obey the law, while for others it is about improving moral character. However, prior studies have reported mixed responses in relation to the issue of providing ethics education. Some have argued that ethics cannot be taught due to several reasons such as students‟ morals or values may be fully developed (Baxter & Rarick, 1987) and firmly entrenched by family or religious institutions (Kultgen, 1988) by the time they enter college. This is because, ethics or morals are learned early in life and by the time students reach college, the students are either honest or not (Levin, 1989). Under this assumption, Levin (1989) believes that unethical behaviour may result from a failure in early learning to distinguish between right and wrong. Therefore, it is argued that teaching ethics at the university level is unlikely to influence students‟ attitudinal changes (Kerr & Smith, 1995; Oddo, 1997; Shenkir, 1990)